Ответы и объяснения

2013-04-25T17:48:30+04:00

у= -3х-7                                            у=-3х-7                                           у=-3х+7

х в кв -(-3х-7)+49=-9х*(-3х-7)       х в кв+3х+7+49=27х+63х           х в кв -87х+56=0

 

 

х в кв-87х+56=0

Д=в в кв -4ас,

Д=(-87)в кв -4*1*56=7569

х1=87-87/2=0

х2=87+878/2=87

 

 

 

х1=0                           х1=0

х2=87                          у1=-3*0+7=0

у=-3х+7                        х2=87

                                      у2=-3*87+7=-268

ОТВЕТ:х1=0;у1=0;

               х2=87;у2=-268.